The Role of Behavioral Science in Personalized Multimodal Prehabilitation in Cancer - Grimmett, Chloe; Bradbury, Katherine; Dalton, Suzanne O.; Fecher-Jones, Imogen; Hoedjes, Meeke; Varkonyi-Sepp, Judit; Short, Camille E. (Frontiers in Psychology, 2021)
Multimodal prehabilitation is increasingly recognized as an important component of the pre-operative pathway in oncology. It aims to optimize physical and psychological health through delivery of a series of tailored interventions including exercise, nutrition, and psychological support. At the core of this prescription is a need for considerable health behavior change, to ensure that patients are engaged with and adhere to these interventions and experience the associated benefits. To date the prehabilitation literature has focused on testing the efficacy of devised exercise and nutritional interventions with a primary focus on physiological and mechanistic outcomes with little consideration for the role of behavioral science, supporting individual behavior change or optimizing patient engagement. Changing health behavior is complex and to maximize success, prehabilitation programs should draw on latest insights from the field of behavioral science. Behavioral science offers extensive knowledge on theories and models of health behavior change to further advance intervention effectiveness. Similarly, interventions developed with a person-centered approach, taking into consideration individual needs and preferences will increase engagement. In this article, we will provide an overview of the extent to which the existing prehabilitation literature incorporates behavioral science, as well as studies that have explored patient's attitudes toward prehabilitation. We will go on to describe and critique ongoing trials in a variety of contexts within oncology prehabilitation and discuss how current scientific knowledge may be enhanced from a behavioral science perspective. We will also consider the role of “surgery schools” and detail practical recommendations that can be embedded in existing or emerging clinical settings.